Mobility and conflict - Sourav Bhattacharya; Joyee Deb; Tapas Kundu (Center for Economic Studies and ifo Institute (CESifo), 2012)
We study the role of inter-group differences in the emergence of conflict. In our setting, two groups compete for the right to allocate societys resources, and we allow for costly intergroup mobility. The winning group offers an allocation, that the opposition can either accept, or reject and wage conflict. Expropriating a large share of resources increases political strength by attracting opposition members, but such economic exclusion implies lower per capita shares and higher risk of conflict. In equilibrium, allocations are non-monotonic in the cost of mobility. Moreover, limited commitment with respect to mobility gives rise to inefficient conflict in equilibrium.
Keywords: D72; D74; D78; P48; 330; conflict; inter-group mobility; political competition; resource allocation; Interessengruppentheorie; Wechselkosten; Konflikt; Wettbewerb; Gleichgewicht; Theorie